Postal survey on airborne occupational exposure and respiratory disorders in Norway: causes and consequences of non-response. Issue 4 (December 1990) - Bakke, P; Gulsvik, A; Lilleng, P; Overå, O; Hanoa, R; Eide, G E
Abstract : STUDY OBJECTIVE--The aim was to examine causes for non-response in a community survey, and how non-response influences prevalence estimates of some exposure and disease variables, and associations between the variables. DESIGN--This was a cross sectional questionnaire study with two reminder letters. The questionnaire asked for information on smoking habits, occupational airborne exposure and respiratory disorders. SETTING--A random sample of 4992 subjects from the general population aged 15-70 years of Hordaland County, Norway. MAIN RESULTS--The overall response rate was 90%, with a 63% response to the initial letter. The response rates to the first and second reminder letters were 56% and 36% respectively. In 20% of the non-respondents an uncompleted questionnaire was returned with cause for non-response; in two thirds of these the cause for non-response was that the subject was not resident at the mailing address. A home visit to a random sample of 50 urban non-respondents provided further information on 29 subjects. A wrong address at the Central Population Registry and the subject's feeling of lack of personal benefit from a postal survey were the major reasons for non-response. Smokers were late respondents and subjects with respiratory disorders tended to be early respondents. CONCLUSION--The main reasons for non-response were a wrong mailing address and a feeling of lack of personal benefit from responding. Using only the initial letter would have changed the estimated prevalence of smokers from 39% to 35%. Otherwise, the estimated prevalence of the exposure and disease variables as well as the associations between them were only slightly changed after including the respondents to the first and second reminder letters.